Dinamika Konflik Anti-Extradition Law Amendment Bill (ELAB) di Hong Kong Tahun 2019 - Soehartono, Amelia Febrianti; Noviryani, Mely (Jurnal Transformasi Global, 2020)
The Conflict of Anti-Extradition Law Amendment Bill (ELAB) in Hong Kong did not appear out of thin air. It was instigated by a Pro-Democracy group to challenge the amendment bill proposed by the government. The conflict escalated when other internal and external actors like the United States expressed their support for the Pro-Democracy group to fight against the Amendment Bill. Using the conflict dynamics approach to examine the process of ELAB conflict, this article analyzes the process through three elements that include internal actors, external parties, and clashes between the Chinese and Hong Kongese in terms of their sociopolitical values. Finally, this research shows that the Hong Kong ELAB conflict had escalated and intensified even more due to the dynamics between these three elements.